An analysis of the pacing strategies adopted by elite athletes during track cycling - Corbett, J. (International Journal of Sports Physiology and Performance, 2009)
Purpose: To investigate pacing strategy during the 1-km time trial (TT) and 3- and 4-km individual pursuit (IP), in elite cyclists. Methods: Total times and intermediate times were obtained from the 2007 and 2008 cycling World Championships in the 1-km TT and 2006, 2007, and 2008 World Championships in the 3- and 4-km IP. Data were analyzed to examine the pacing-profiles employed and pacing strategies of "slow" and "fast" performances. Results: Similar pacing-profiles were evident in each event, which were characterized by an initial acceleration followed by a progressive decay in split times. In the 1-km TT, the first 250-m split time was a primary determinant of total time, whereas the rate of fatigue over the remainder of the race did not discriminate between performances. The first 250-m split time was also related to total time in the 3- and 4-km IP, although to a lesser extent than in the 1-km TT, whereas the ability to maintain a consistent pacing-profile was of increased importance. There were differences in the pacing strategies of slow and fast performances in the 3- and 4-km IP, with slow performances characterized by an overly quick start with a concomitant slowing at the finish. Conclusion: The pacing profiles adopted were similar to the optimal pacing strategies proposed in simulation models of cycling performance. However, in the 3-km and 4-km IP small alterations in pacing strategy appear to be important, at the elite level.